Effect of ultrasonic treatment on structural transformations and mechanical behaviour of amorphous alloys (REVIEW) - Inga E. Permyakova; Elena V. Dyuzheva-Maltseva (Frontier Materials & Technologies)
The wide application of amorphous alloys is complicated by a narrow range of their thermal stability, embrittlement at elevated temperatures, difficult machinability, and low tensile plasticity. Ultrasonic treatment is an innovative method for solving these problems. Integration of ultrasonic technology into the technological chain can contribute to the improvement of the operational property of amorphous alloys, the manufacture of parts from them at different scale levels, and high-quality joining with other materials. The effect of ultrasonic vibrations on structural transformations and mechanical behaviour of amorphous alloys is not completely understood. The lack of an integrated scientific basis for the physical processes and accompanying effects in amorphous alloys under ultrasonic excitation prevents the development of the corresponding technology and optimization of its modes. Over the past decade, researchers have proposed various methods of ultrasonic treatment of amorphous alloys to improve their formability, achieve a balance of plasticity and strength, and consolidate with each other and with metals. In addition, certain ideas have been developed about their structure rejuvenation and the possibilities of transformation them to a partially nanocrystalline state under the action of ultrasound. To summarise these developments, the systematic discussion on features, parameters, and modes of ultrasonic treatment applied to ribbon and bulk amorphous alloys to improve their structure-sensitive properties are provided in this review. On this basis, the limitations of current study are discussed. The most promising applications of ultrasonic technologies for rapidly melt-quenched alloys in the near future include: their additive manufacturing, creation of hybrid composites by ultrasonic welding, ultrasonic forming for manufacturing products of complex shapes and geometries, complex multi-stage processing to obtain a unique combination of properties (e.g., melt quenching → laser irradiation → ultrasonic stimulation). This review enhances the existing knowledge on ultrasonic control of the properties and structure of amorphous alloys and facilitates a fast references on this topic for researchers.